Investigating temporal microbial dynamics in the rumen of beef calves raised on two farms during early life. Issue 2 (9th January 2020) - O'Hara, Eóin; Kenny, David A; McGovern, Emily; Byrne, Colin J; McCabe, Matthew S; Guan, Le Luo; Waters, Sinéad M
ABSTRACT: Manipulation of the rumen microorganisms during early life has emerged as a promising strategy for persistent improvement of nutrient utilisation and lowering of enteric methanogenesis. However, limited understanding of the dynamics of rumen microbial colonisation has prevented the identification of the optimum timeframe for such interventions. The present study used DNA amplicon sequencing of the 16S rRNA gene to assess bacterial and archaeal dynamics in the rumen digesta of beef calves raised on two farms from birth through to post-weaning. The colonisation patterns of both communities were influenced by age ( P < 0.05) and farm of origin ( P < 0.05). The bacterial community exhibited an age-wise progression during the first month of life which appeared to be partly related to diet, and settled by day 21, indicating that this may mark the boundary of a timeframe for intervention. The archaeal community appeared less sensitive to age/diet than bacteria in the first month of life but was more sensitive to farm environment. These data show that ruminal microbial composition during early life is driven by calf age, diet and local environment, and provide important fundamental information concerning the ontogeny of the rumen microbiota from birth. Abstract : Rumen microbial establishment patterns in early life are influenced by calf age, dietary management and farm of origin.